Potassium titanyl phosphate laser surface tympanoplasty as a novel treatment for chronic granular myringitis in a series of 14 patients. Issue 11 (22nd November 2022) - Ghedia, R; Sutton, L; Hogan, C; Seymour, K; Wareing, M
Abstract: Objective: Granular myringitis is a chronic and difficult-to-treat condition of the tympanic membrane. This paper presents a minimally invasive treatment technique using the potassium titanyl phosphate laser. Design: A retrospective case review of patients who underwent potassium titanyl phosphate laser treatment between 2015 and 2020 was performed. All patients underwent final telephone follow up in 2020 to ascertain whether they had any ongoing myringitis symptoms, and all were offered further face-to-face follow up. Results: Fourteen patients with myringitis were identified, with one patient having both ears affected. Of the 15 affected ears, 2 required a second treatment, resulting in a total of 17 laser treatment cases. At the first post-operative review, the appearance of the drum had improved in 10 out of 17 treatments (59 per cent). Conclusion: Potassium titanyl phosphate laser surface tympanoplasty may provide safe, quick and effective resolution of myringitis.